2022
DOI: 10.3389/fnagi.2021.826213
|View full text |Cite
|
Sign up to set email alerts
|

ADHD and Neurodegenerative Disease Risk: A Critical Examination of the Evidence

Abstract: In this review, we undertake a critical appraisal of eight published studies providing first evidence that a history of attention-deficit/hyperactivity disorder (ADHD) may increase risk for the later-life development of a neurodegenerative disease, in particular Lewy body diseases (LBD), by up to five-fold. Most of these studies have used data linked to health records in large population registers and include impressive sample sizes and adequate follow-up periods. We identify a number of methodological limitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 99 publications
(191 reference statements)
0
16
0
Order By: Relevance
“…Dissociating typical from pathological attention functioning during aging is a current challenge in clinical settings. For example, attention deficit would be a risk or a prodrome of Alzheimer’s or Parkinson’s disease (Becker et al, 2022; Cammisuli et al, 2021; Zhang et al, 2022). Detecting early and subtle abnormal attention changes during aging could thus contribute to estimate the risk of developing neurodegenerative disease (Becker et al, 2022) and might also help to define the evolutionary stage of the disease (Del Tredici & Braak, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dissociating typical from pathological attention functioning during aging is a current challenge in clinical settings. For example, attention deficit would be a risk or a prodrome of Alzheimer’s or Parkinson’s disease (Becker et al, 2022; Cammisuli et al, 2021; Zhang et al, 2022). Detecting early and subtle abnormal attention changes during aging could thus contribute to estimate the risk of developing neurodegenerative disease (Becker et al, 2022) and might also help to define the evolutionary stage of the disease (Del Tredici & Braak, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For example, attention deficit would be a risk or a prodrome of Alzheimer’s or Parkinson’s disease (Becker et al, 2022; Cammisuli et al, 2021; Zhang et al, 2022). Detecting early and subtle abnormal attention changes during aging could thus contribute to estimate the risk of developing neurodegenerative disease (Becker et al, 2022) and might also help to define the evolutionary stage of the disease (Del Tredici & Braak, 2020). We are now working to determine whether the CAT is a reliable and sensitive measure for dissociating subclinical and clinical attention difficulties.…”
Section: Discussionmentioning
confidence: 99%
“… 12 , 94 Working memory and/or cognitive control—two RDoC subconstructs associated with cognitive system—are impaired in ADHD, ASD, mild intellectual disability, and borderline intellectual functioning. 7 , 104 , 138 , 139 Several studies have shown an increased risk of developing neurodegenerative disease during later life for patients with a history of ADHD, 140 including a large multi-generation cohort study in Sweden that associated ADHD with AD and any dementia across generations. 141 However, well-designed prospective longitudinal studies are necessary to reassure the validity of estimated neurodegenerative risk for patients with ADHD.…”
Section: Orx-s Dysfunction and Main Symptom Domain Of Essence Within ...mentioning
confidence: 99%
“… 141 However, well-designed prospective longitudinal studies are necessary to reassure the validity of estimated neurodegenerative risk for patients with ADHD. 140 Future studies would preferably also investigate the possible role of an underlying Orx-S dysfunction.…”
Section: Orx-s Dysfunction and Main Symptom Domain Of Essence Within ...mentioning
confidence: 99%
See 1 more Smart Citation